2008
DOI: 10.1093/nar/gkn049
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ku70/Ku80 association with full-length RAG1

Abstract: Antigen receptor genes are assembled by a site-specific DNA rearrangement process called V(D)J recombination. This process proceeds through two distinct phases: a cleavage phase in which the RAG1 and RAG2 proteins introduce DNA double-strand breaks at antigen receptor gene segments, and a joining phase in which the resulting DNA breaks are processed and repaired via the non-homologous end-joining (NHEJ) repair pathway. Genetic and biochemical evidence suggest that the RAG proteins play an active role in guidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 54 publications
2
51
0
Order By: Relevance
“…S1A). MBP cRAGs (RAG1, amino acids 384 -1040; RAG2, amino acids 1-383) and full-length RAGs (FLRAG1, 1-1040 amino acids; FLRAG2, 1-527 amino acids) were purified using a mild method as described (40). Briefly, 14 plates of 293T cells were transfected with 10 g of plasmids each for MBP cRAG1/cRAG2 or cRAG1/FLRAG2 by the calcium phosphate method.…”
Section: Methodsmentioning
confidence: 99%
“…S1A). MBP cRAGs (RAG1, amino acids 384 -1040; RAG2, amino acids 1-383) and full-length RAGs (FLRAG1, 1-1040 amino acids; FLRAG2, 1-527 amino acids) were purified using a mild method as described (40). Briefly, 14 plates of 293T cells were transfected with 10 g of plasmids each for MBP cRAG1/cRAG2 or cRAG1/FLRAG2 by the calcium phosphate method.…”
Section: Methodsmentioning
confidence: 99%
“…One possibility is that NHEJ factors stabilize the coding ends in the post-cleavage complex, increasing the time available for their attack by the RSS ends. In support of this, flRAG1, but not cRAG1, appears to associate with the Ku70/80 NHEJ protein in co-immunoprecipitation assays (Raval et al 2008). …”
Section: Transposition and Other Nonstandard Dna Transactionsmentioning
confidence: 85%
“…importin alpha 5, SRP1, and RAG cohort protein 2 (Cortes et al 1994)), karyopherin alpha 2 (KPNA2, a.k.a. RAG cohort protein 1 (Cuomo et al 1994)), and possibly the NHEJ factor Ku (Raval et al 2008). KPNA2 binds to a nuclear localization signal within the core and is necessary and sufficient for nuclear import of RAG1 (Spanopoulou et al 1995).…”
Section: Kpna1 Binding and Ubiquitylationmentioning
confidence: 99%
“…A more recent report provides evidence for an interaction between RAG1 and Ku70/Ku80 (30). This interaction is also mediated by the N-terminal non-core region of RAG1 and affects signal joint formation.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence for an interaction between RAG1 and Ku70/Ku80 represents the only known link between RAG and a repair factor (30). An early report showed that ␥-H2AX and NBS1 form RAG-dependent foci that correspond to actively rearranging loci in thymocytes (31).…”
mentioning
confidence: 99%